Formation Control of Multi-Robot using Virtual Structures with a Linear Algebra Approach - Arfittariah Riah; Trihastuti Agustinah (JAREE (Journal on Advanced Research in Electrical Engineering), 2020)
The separation bearing controller (SBC) and separation-separation controller (SSC) approaches can be used to maintain multi-robot formation, while the Computed Torque Control (CTC) method is used to solve the dynamic problems of the robot. However, the SBC and SSC approaches combined with CTC cannot maintain multi-robot formation, if the leader or follower is disturbed. In this paper, the virtual structure method and the linear algebra approach added to the CTC method are used to maintain the triangular robot formation to follow the given trajectory. The simulation results show that the proposed control system design of multi-robots capable of following the trajectory and can maintain multi-robot formation with/without disturbance and noise.Keywords: computed torque control,  formation control, linear algebra, trajectory tracking, virtual structure.